The effect of active rheumatoid arthritis on hearing impairment - Hayder Kadhim Essa; Hussain Hasan; Hassan Thabit Saeed (Journal of the Pakistan Medical Association, 2024)
Objective: To assess hearing loss in rheumatoid arthritis (RA) patients, and to explore its association with disease attributes and activity. Method: The cross-sectional case-control study was conducted from June to December 2022 at Al-Imamein Al-Kadhimein Hospital, Medical City, Baghdad, Iraq, and comprised rheumatoid arthritis patients and healthy controls of either gender aged 18-45 years. Data was collected using electronic instruments and a physical examination, including pure tone audiometry and tympanogram. Data was analysed using SPSS 24. Results: Of the 90 subjects, 60(66.7%) were patients; 45(75%) female and 15(25%) males with mean age 32.9 1±7.21 years and mean body mass index 27.14±8.58kg/m2. There were 30(33.3%) controls; 18(60%) female and 12(40%) males with mean age 30.25±5.51 years and mean body mass index 26.92±6.66kg/m2. The control group had thresholds below 25dB for all frequencies in both ears, which were notably lower than those of the RA patients (p=0.005). The left ear showed significant variation at 2000Hz and 4000Hz, while the right ear showed substantial differences at all frequencies except 1000Hz. Conclusion: The risk of hearing loss was found to be increased in rheumatoid arthritis patients, and it seemed to be related to illness duration. Key Words: Audiometry, Arthritis, Rheumatoid, Electronics,